The Effect of Pressure Training Exercises in the Development of Special Endurance and Accomplish the 400m Run of Young Women - Qahtan Abdul Mohsen, Zainab (International Journal of Psychosocial Rehabilitation, 2020)
The event of running 400 m is one of the events characterized by strength, speed, and endurance. Through these features, it was considered one of the short sprint events that's relatively long. By observing the results of achievement levels in the Iraqi women's 400m run event, a clear weakness in the levels of achievement is found. Thus, the problem of research is formed, which directed the preparation of exercises in the pressure training method to develop special endurance and achieve 400 meters for young women. The experiment is applied to (5) players of the women's team of the faculty of physical education and sciences sports for women. It has concluded that the training pressure exercises have a positive effect on the development of special endurance variables and the achievement of 400 m.